2009
DOI: 10.1021/la803710d
|View full text |Cite
|
Sign up to set email alerts
|

Silicon (100) Electrodes Resistant to Oxidation in Aqueous Solutions: An Unexpected Benefit of Surface Acetylene Moieties

Abstract: Here we report on the functionalization of alkyne-terminated alkyl monolayers on highly doped Si(100) using "click" reactions to immobilize ferrocene derivatives. The reaction of hydrogen-terminated silicon surfaces with a diyne species was shown to afford very robust functional surfaces where the oxidation of the underlying substrate was negligible. Detailed characterization using X-ray photoelectron spectroscopy, X-ray reflectometry, and cyclic voltammetry demonstrated that the surface acetylenes had reacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
240
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(260 citation statements)
references
References 84 publications
20
240
0
Order By: Relevance
“…Longer linkers act as dielectrics and hamper the electron flow. [66][67][68] Dubacheva and co-workers recently demonstrated the binding of ferrocene polymers into the hydrophobic pocket of CD. The CDs were introduced by using click chemistry on preformed SAMs on gold surface; they showed the association and dissociation of ferrocene polymers into CD during the redox process.…”
Section: Surface Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer linkers act as dielectrics and hamper the electron flow. [66][67][68] Dubacheva and co-workers recently demonstrated the binding of ferrocene polymers into the hydrophobic pocket of CD. The CDs were introduced by using click chemistry on preformed SAMs on gold surface; they showed the association and dissociation of ferrocene polymers into CD during the redox process.…”
Section: Surface Adsorptionmentioning
confidence: 99%
“…The application of voltage across the functionalized electrode resulted in uncapping due to the oxidation of ferrocene to ferrocenium species. [67] Nanomaterials and Supramolecular Assemblies Nanotubes, nanofibers, and other nanoscale materials show unusual properties in catalysis, electrical conductivity, the design of lightweight materials, and so on relative to the bulk matter. Functionalization of the surface of these nanomaterials with specially designed molecules promises the generation of materials with extraordinary functions.…”
Section: Surface Adsorptionmentioning
confidence: 99%
“…[79,80] Indeed, reducing the surface density of the alkyne moieties is helpful to improve "click" coupling efficiencies, as demonstrated for organic monolayers composed of a mixture of 1,8-nonadiyne/1-heptyne. [61] With progressive dilutions of the diyne mole fraction from 1.00 to 0.05, close to quantitative yield was achieved according to the electrochemical characterization. However, this approach does not actually improve the surface density of the immobilized molecules.…”
Section: Optimization Of the Cuaac Reaction Conditions On An Alkyne-pmentioning
confidence: 91%
“…Both the presence of a distal alkyne moiety and temperatures of formation above 100 8C were critical to achieve this surface stabilization. [61] By taking advantage of the same platform developed by Gooding s group, Liu et al have also demonstrated the first example of attaching b-azidometalloporphyrins on a SiA C H T U N G T R E N N U N G (100) substrate. [62] The high-quality modified silicon electrodes with well-defined electrochemistry open the door to using such surfaces in biosensing and memory devices.…”
Section: Preparation Of Alkyne-terminated Monolayers and The Subsequementioning
confidence: 99%
See 1 more Smart Citation